Tetramethoxy resorcinarens as platforms for fluorescent and halogen bonding systems - Tero, Tiia-Riikka (2015)
The synthesis and characterization of new tetramethoxy resorcinarene derivatives are described. The new compounds are obtained and characterized in solution and solid state, along with halogen bonded networks. In the coming pages the structural and photophysical properties of newly synthesized tetramethodxy resorcinarene derivatives will be presented. A previously unknown derivative of the tetramethoxy resorcinarene platform, methyl tetramethoxy resorcinarene, was synthesized completing the family of tetramethoxy resorcinarenes. Methyl C1- and ethyl C2-tetramethoxy resorcinarenes were used as platforms for the syntheses of five different pyridine and benzyl functionalized resorcinarene tetrapodands, and for the crown-ether bridged benzofuran resorcinarene derivative. The structural properties of these compounds were studied in solution by NMR spectroscopy and in the solid state by X-ray crystallography. Only one carbon difference in the lower rim alkyl groups, methyl vs. ethyl, was observed to affect the dynamic behavior of resorcinarene podands in solution. In the solid state, methyl tetramethoxy resorcinarene obeyed compact “brick”-like packing made possible by the small methyl group at the lower rim. The pyridine functionalized resorcinarene podands were used in the construction of solid state halogen bonded architectures with halobenzene linkers. The structural characteristics of the resorcinarene scaffold and the podand arms allowed the formation of multidimensional networks showing potentially porous properties. In solution, although no formation of larger assemblies were observed, halogen bonding between resorcinarenes and the linkers was confirmed; and the observed interactions were supported by computational methods. In the synthesis of crown bridged resorcinarenes, a side product was isolated that contained an unusual benzofuran fused macrocyclic structure. The modified macrocycle had characteristic fluorescence properties and the study showed that emission/excitation matrix spectroscopy is a valid tool for structure analysis in solution.